PENERAPAN MODEL INTEGRASI FUZZY SERVQUAL-IPA-QFD DALAM ANALISIS KUALITAS LAYANAN STASIUN GAMBIR - Sukwadi, Ronald; Josua, Priskilla Putri; Tannady, Hendy (Universitas Tarumanagara, 2021)
Public transportation has been regarded as one of the most sustainable forms of transport in Indonesia. Indonesian Railways serves as one of choice transportation mode and the biggest transportation service company. Gambir Central Station is the busiest railway platform where large number of people spend considerable amount of time, while waiting to board a train, alighting from a train, to receive/ send off a passenger, or to buy a ticket. The passengers must have a satisfactory experience of the amenities available at platforms, irrespective of their duration or purpose of stay at a railway station. This study aims to assess the satisfaction level of the passengers and to improve the existing service quality of the station. The integrated model of fuzzy SERVQUAL, IPA and QFD is applied in this study. The fuzzy SERVQUAL is used to assess the level of passengers’ satisfaction. Furthermore, the Importance Performance Analysis (IPA) method is used to find out the attributes that must be improved. The Quality Function Deployment (QFD) method is used to determine the appropriate efforts/strategies to improve those attributes. To meet the passengers’ needs, Gambir Central Station should install a hygiene signboard, conduct training of officers, and add greening areas. Keywords: Service quality, Fuzzy SERVQUAL, IPA, QFD, Railway station AbstrakAngkutan umum telah dianggap sebagai salah satu bentuk transportasi paling berkelanjutan di Indonesia. Kereta Api Indonesia menjadi salah satu moda transportasi pilihan dan perusahaan transportasi terbesar. Stasiun Gambir adalah stasiun tersibuk di mana banyak orang menghabiskan banyak waktu, menunggu untuk naik kereta, turun dari kereta, keluar/masuk penumpang, atau membeli tiket. Penumpang harus memiliki pengalaman yang memuaskan tentang fasilitas yang tersedia di stasiun, terlepas dari durasi atau tujuan mereka tinggal di stasiun kereta api. Penelitian ini bertujuan untuk menilai tingkat kepuasan penumpang dan meningkatkan kualitas pelayanan stasiun yang ada. Model terintegrasi fuzzy SERVQUAL, IPA dan QFD diterapkan dalam penelitian ini. Fuzzy SERVQUAL digunakan untuk menilai tingkat kepuasan penumpang. Selanjutnya, Importance Performance Analysis (IPA) digunakan untuk mengetahui atribut-atribut yang harus ditingkatkan. Metode Quality Function Deployment (QFD) digunakan untuk menentukan upaya/strategi yang tepat untuk memperbaiki atribut tersebut. Untuk memenuhi kebutuhan penumpang, Stasiun Gambir harus memasang papan tanda kebersihan, melakukan pelatihan petugas stasiun, dan melakukan penambahan area penghijauan.